FORECASTING THE ECONOMIC DEVELOPMENT OF INDUSTRIAL POTENTIAL ON THE BASIS OF TREND MODELS IN THE SUSTAINABLE DEVELOPMENT OF INDUSTRY IN SAMARKAND REGION - Yakhshilikov Jasur Juraboyevich (Scholar Express Journals, 2022)
This article analyzes the factors of sustainable development of the manufacturing industry of the regions. At the same time, proposals and conclusions have been developed through the analysis and forecasting of the state of industrial potential in sustainable development. The object of research is the regional industry of Samarkand region.
Keywords: Econometrics; trend model; industry; sustainable development